The phenomenon of exclusion of vulnerable groups in cityCommunity : Analytical theory study of causes and factors - Sahbi, Wahiba (Journal of Architecture and environment of child, 2022)
This study aims to identify the most important marginalized categories within urban society and the most important factors leading to this. Considering that during the phases and periods of its growth, the city is subject to implicit mechanisms and contradictions that go beyond the principles, objectives, and plans of urban development, as well as the regulations and provisions of the legislation controlling the city's urbanization, it has led to the dismantling and reinstallation of the population community characteristics, which have affected the morphology of the city and its life characteristics. Social and urban imbalances in cities have emerged at several levels, such as the widening gap between welfare neighborhoods and poverty neighborhoods, which has led to a significant disparity in the level of urban services and facilities provided. These factors have thus created social exclusions, particularly within urban communities. The study concluded the need to develop a comprehensive assessment perspective based on the systems of social and economic indicators in cities to understand and analyze the phenomena of social exclusion as a necessity to improve the level of life in the city. This is done through developing strategies to ensure the achievement of mechanisms for adaptation, integration and coping in the receiving environment of individuals who are subject to the repercussions of urbanization and migration. The aim is to ensure their status and urban life, and to live with the changes taking place under the system of societal and economic transformations that cities are undergoing.